PERBANDINGAN KINERJA FILLER SLAG NIKEL DENGAN KAPUR PADAMAN DALAM CAMPURAN HRS (HOT ROLLED SHEET) - Edward Ngii (Metropilar - Jurnal Ilmiah Fakultas Teknik, 2008)
Aggregate materials used in asphalt mixture is based on assumption which is materials came from the same sources, quality, and heaving the same specific gravity or almost same. There for the used of alternative filler in HRS mixture need to examinated to find filler content that produce the optimum asphalt content as reference of mix performance. This research conducted to HRS-Wearing Course type. Kind of alternative fillers in this research are hydrated lime filler and slag nickel filler. Material testing based on AASHTO/ASTM standard while filler content variation of hydrated lime filler and slag nickel filler are 1%; 3%; 5%; 7% and 9%. At each variation of comparison filler was made sample by asphalt content : 6,0%;  6,5%; 7,0%;  7,5% and 8,0%. Each specimen conducted the examination through the Marshall Test apparatus. Determination of the optimum asphalt content based on the narrow range method, conformed to the 2002 specifications of Kimpraswil Department. Result researched found that using filler content of 7% of hydrated lime can produce the optimum asphalt content (7.63%) and using filler content of 1% of slag nickel can produce the optimum asphalt content (6,75%).  Stability value compare to  dust filler is higher (1910.41 kg) than hydrated lime (1489.20 kg) and slag nickel filler (1525.40 kg) The value that is obtained from both fillers substitution is still fulfill the 2002 specifications of Kimpraswil Department for HRS-WC that is stability value recommended more than 800 kg.   Key Words: filler, nickel slag, hydrated lime, HRS Mixture